Studying the influence of uv adsorbers on optical characteristics of light-protective polymer films for textile materials - Semeshko, Olga; Pasichnyk, Maria; Hyrlya, Lyudmila; Vasylenko, Viktoria; Kucher, Elena (Eastern-European Journal of Enterprise Technologies, 2019)
The use of UV adsorbers included in composition of a polymer film is a promising way of color protecting against effects of light since application of the polymer to the textile material surface is a universal way of providing the textile materials with necessary special properties. Optical characteristics are the most important indicators of suitability of polymer films for their use in final processing of colored textile materials. The objective of this study consisted in a spectrophotometric determination of optical characteristics of polymer films based on a styrene-acrylic polymer with addition of a cross-linking agent and UV adsorbers for the use in final processing of textile materials for the purpose of their color protection. The polymer matrix is an aqueous dispersion of a thermally linking styrene-acrylic copolymer. Partly esterified melamine resin was used as a cross-linking agent and 2,4-dihydroxybenzophenone, 3,6-dihydroxyacetophenone, salicylic acid phenyl ether, p-methoxy cinnamic acid were used as UV adsorbers. Optical characteristics of polymer films were determined using SF-56 spectrophotometer by constructing spectral curves of absorption and transmission in the range of 200‒800 nm. Based on analysis of spectral curves of absorption in polymer films, UV adsorbers which provide formation of colorless polymer films have been established. Spectral curves of light transmission of the studied polymer films in the visible portion of spectrum have allowed us to determine effect of UV adsorbers on film transparency and light transmission in relation to UV rays in the UV portion of the spectrum. Substances that contribute to reduction of UV radiation transmission through polymeric films and provide light protection properties were established. Based on the multivariate analysis of the results obtained in the study of optical characteristics of polymer films, a composition based on styrene-acrylic polymer, cross-linking agent and UV adsorber was recommended. The found composition is suitable for its use in final processing of colored textile materials in order to form a colorless, transparent coating with light-protective properties.